# Devin made some mistakes. Identify where he made each mistake: 24 ÷ 6 x (5 – 1) = 24 ÷ 6 x 4 = 24 ÷ 24 = 1

Answer: When doing the order of operations and you are put in a situation where you do two different operations, solve the problem from left to right.
In this case instead of doing 6*4 first do 24/6 first.

## Related Questions

The game of heads up is played by flipping two coins. If they both land heads up, you win \$8. If only one lands heads up, you win \$14. If no coins land heads up, you win \$0. If you pay \$6 to play the game each time the coins are flipped, is the game a fair game? Why or why not?

The game of heads up is played by flipping two coins. The game is a fair game

Solution:

Given that , the game of heads up is played by flipping two coins.

If they both land heads up, you win \$8.

And If only one lands heads up, you win \$14.

And If no coins land heads up, you win \$0.

We have to pay \$6 to play the game each time the coins are flipped,

Then we have to find is the game a fair game

Now, we say a thing is fair if it is favorable for us.

From players view, to say the game is fair, we have to get money.

Now, if we see

When we pay \$6, we will lose it only when no heads are up as we get \$0 in that condition.

But we will get 14 – 6 = \$8 when one head turns up and 8 – 6 = \$2 when both heads are up.

Now, number of outcomes for losses = 1 (tail – tail condition)

Probability =

Probability =

Clearly we can say that, chances of winnings are more.

Hence, it is an fair game.

Question 11 of 20 : Select the best answer for the question. 11. Find the value of x in the equation 2(x – 3) + 5x = 5(2x + 6). A. 2 B. –12 C. 12 D. –2

To answer this question, you need to know the rules to move a number to the left or right side of the equal sign. To solve this, you need to move all the x into one side, and then move the number into another side. The calculation would look like this:

2(x – 3) + 5x = 5(2x + 6)
2x -6 +5x = 10x +30
2x+ 5x - 10x = 30 +6
-3x= 36
x= 36/-3= -12
I got -12

2(x-3)+5x=5(2x+6)
2x-6+5x=10x+30
7x-6=10x+30
-3x=36

Which equation could be used to find the length of the hypotenuse? 5 cm
8 cm
o 5² +8² = c²
o 5²+0²= 8²
o c² – 5² = 8²
O 8²_5² = 0²

5^2 + 8^2 =c^2 is the answer

explanation

Pythagoras theorm a^2+b^2=c^2

both 5 and 8 can be either be a or b

a or b

Step-by-step explanation:

F(x) = 5x + 10
g(x) = 3x² + 10x + 6
Find: f(x) · g(x)